Antibiotik Topikal pada Tatalaksana Impetigo - Verra Rachma Indahsari (Jurnal Medika Hutama, 2021)
Background. Impetigo is a contagious superficial bacterial skin infection that affects people of all ages but is more common in children. Staphylococcus aureus is the main causative pathogen despite Streptococcus pyogenes or both. Complications of impetigo are rare, but local and systemic spread of infection can occur. So it is an important reason for the need for antibiotic treatment that can speed up the resolution of symptoms. Method. This research is a literature review involving 17 literature sources with the keywords used include ‘impetigo, treatment, topical antibiotics and resistance '. Result. Several studies have shown resistance to the use of topical antibiotics in the treatment of impetigo, for example the antibacterial agents fusidic acid and mupirocin, and may continue to increase. Ozenoxacin has been shown in several studies to have strong antibacterial activity against staphylococci and streptococci, a rapid bactericidal effect and a low potential for resistance. Conclusion. Antibiotic interventions for impetigo are currently relatively effective, but patterns of bacterial resistance are changing. Ozenoxacin can be a useful alternative for treating impetigo in children and adolescents